A 5(4) pair explicit Runge-Kutta-Nystrom method for solving oscillatory problems - Senu, Norazak; Suleiman, Mohamed (Global Information Publisher, 2009)
A new 5(4) pair embedded explicit Runge-Kutta-Nyström method is developed to integrate second-order differential equations of the form y"=f (x,y)where the solution is oscillatory. The embedded formula has dispersive order eight and dissipative order five for the fifth-order 5(4) pair. The 5(4) pair cost four function evaluations at each step of integration. Nu- merical comparisons with current methods such as DOPRI5, RKN5(4)D and RKN5(4)B show the efficiency of the new method developed.